A novel two-section tunable discrete mode Fabry-Perot laser exhibiting nanosecond wavelength switching - DONEGAN, JOHN; GUO, WEI-HUA; LU, QIAOYIN (My University, 2008)
A novel widely tunable laser diode is proposed and demonstrated. Mode selection occurs by etching perturbing slots into the laser ridge. A two-section device is realized with different slot patterns in each section allowing Vernier tuning. The laser operates at 1.3 m and achieves a maximum output power of 10 mW. A discontinuous tuning range of 30 nm was achieved with a side mode suppression greater than 30 dB.Wavelength switching times of approximately 1.5 ns between a number of wavelength channels separated by 7 nm have been demonstrated.
PUBLISHED
Keywords: Fast wavelength switching, semiconductor laser diode, Vernier effect, widely tunable laser.